In Situ Cultured Bacterial Diversity from Iron Curtain Cave, Chilliwack, British Columbia, Canada - Soumya Ghosh; Elise Paine; Rob Wall; Gabrielle Kam; Tanna Lauriente; Pet-Chompoo Sa-ngarmangkang; Derrick Horne; Naowarat Cheeptham (Diversity, 2017)
The culturable bacterial diversity from Iron Curtain Cave, Chilliwack, British Columbia, Canada was examined. Sixty five bacterial isolates were successfully cultivated, purified, and identified based on 16S rRNA gene sequencing. Four distinguishable phyla, i.e., Actinobacteria (44.61%), Proteobacteria (27.69%), Firmicutes (20%) and Bacteroidetes (7.69%) were identified. Arthrobacter (21.53%) was identified as the major genus, followed by Sporosarcina (9.23%), Stenotrophomonas (9.23%), Streptomyces (6.15%), Brevundimonas (4.61%), and Crocebacterium (2.8%). Noteworthy, 12.3% of the population was recognized as unidentified bacteria. The isolates were evaluated for their potential antimicrobial activities against multidrug resistant microbial strains. Two species of the genus Streptomyces exhibited a wide range of antimicrobial activities against multidrug resistance (MDR) strains of Escherichia coli and Pseudomonas spp. along with non-resistant strains of Staphylococcus aureus and E. coli. However, all of the antimicrobial activities were only observed when the isolates were grown at 8 °C in different media. To the best of our knowledge, this is the first study conducted on the Iron Curtain Cave’s bacterial diversity, and reveals some bacterial isolates that have never been reported from a cave. Bacterial isolates identified with antimicrobial properties demonstrated that the Iron Curtain Cave can be further considered as a potential habitat for antimicrobial agents.